External Economic Situation in India - Recent Trends and Policy Implications - Planning Commission (Planning Commission, 1999)
The paper reviews status of the external sector of the Indian economy. It discusses the trends of imports & exports and direction of external trade since 1984-85, alongwith recent trends in balance of payments, external debt, foreign exchange movements and foreign investment. The factors that have led to recent slow down in trade and investment in India are examined. The paper also looks at the South-East Asian crisis and the recent global trends and their impact on India's trade prospects. In addition, some of the important areas of concern relating to the agreements under the WTO have also been discussed. In light of various domestic and international developments, the lessons that emerge for India are brought out.
Perspective Planning Division Planning Commission Government of India